What Works When Treating Granulomatous Disease in Genetically Undefined CVID? A Systematic Review - van Stigt, Astrid C.; Dik, Willem A.; Kamphuis, Lieke S. J.; Smits, Bas M.; van Montfrans, Joris M.; van Hagen, P. Martin; Dalm, Virgil A. S. H.; IJspeert, Hanna (Frontiers in Immunology, 2020)
Background Granulomatous disease is reported in at least 8-20% of patients with common variable immunodeficiency (CVID). Granulomatous disease mainly affects the lungs, and is associated with significantly higher morbidity and mortality. In half of patients with granulomatous disease, extrapulmonary manifestations are found, affecting e.g. skin, liver and lymph nodes. In literature various therapies have been reported, with varying effects on remission of granulomas and related clinical symptoms. However, consensus recommendations for optimal management of extrapulmonary granulomatous disease are lacking. Objective To present a literature overview of the efficacy of currently described therapies for extrapulmonary granulomatous disease in CVID (CVID+EGD), compared to known treatment regimens for pulmonary granulomatous disease in CVID (CVID+PGD). Methods The following databases were searched: Embase, Medline (Ovid), Web-of-Science Core Collection, Cochrane Central and Google Scholar. Inclusion criteria were 1) CVID patients with granulomatous disease, 2) treatment for granulomatous disease reported, and 3) outcome of treatment reported. Patient characteristics, localization of granuloma, treatment, and association with remission of granulomatous disease were extracted from articles. Results We identified 64 articles presenting 95 CVID patients with granulomatous disease, wherein 117 different treatment courses were described. Steroid monotherapy was most frequently described in CVID+EGD (21 out of 53 treatment courses) and resulted in remission in 85.7% of cases. In CVID+PGD steroid monotherapy was described in 15 out of 64 treatment courses, and was associated with remission in 66.7% of cases. Infliximab was reported in CVID+EGD in 6 out of 53 treatment courses and was mostly used in granulomatous disease affecting the skin (4 out of 6 cases). All patients (n=9) treated with anti-TNF-α therapies (infliximab and etanercept) showed remission of extrapulmonary granulomatous disease. Rituximab with or without azathioprine was rarely used for CVID+EGD, but frequently used in CVID+PGD where it was associated with remission of granulomatous disease in 94.4% (17 of 18 treatment courses). Conclusion Although the number of CVID+EGD patients was limited, data indicate steroid monotherapy often results in remission, and that anti-TNF-α treatment is effective for granulomatous disease affecting the skin. Also, rituximab with or without azathioprine was mainly described in CVID+PGD, and only in few cases of CVID+EGD.